Boost for UUM graduates: Professional body CILTM recognises varsity's logistic programme - M.Ali, Sharidan (The Star, 2011)
KUALA LUMPUR: A memorandum of agreement (MoA) signed between Chartered Institute of Logistic and Transport Malaysia (CILTM) and Universiti Utara Malaysia (UUM) recently will act as a springboard for the latter's graduates in Logistic studies to enter the industry.